P-061 Impact of Dose Escalation with Anti-TNFs on Healthcare Resource Utilization Among Patients with Crohn's Disease: A Multi-Country Chart Review. (February 2017) - Pérez Gisbert, Javier; Patel, Haridarshan; Nguyen, Geoffrey; Bokemeyer, Bernd; Armuzzi, Alessandro; Lindsay, James; Khalid, Javaria; Peyrin-Biroulet, Laurent
Abstract : Background: Patients with Crohn's disease (CD) treated with tumor necrosis factor antagonists (anti-TNF) may lose response to therapy over time. In these patients, dose escalation is a common strategy to try and recapture response. Previous studies have shown that more than 10% of patients lose response and require dose escalation. 1 However, the overall impact on health care resource utilization (HCRU) of this strategy remains largely unknown. Our aim was to measure the incidence of dose escalation and describe the impact on HCRU among patients whose dose was escalated with anti-TNF therapies in real-world clinical practice. Methods: A retrospective chart review study conducted in 6 countries (Canada, France, Germany, Italy, Spain, and United Kingdom) recruited CD patients (≥18 yr old) initiating an anti-TNF therapy (infliximab or adalimumab) for the first time between June 2009 and June 2011. Dose escalation was defined as either a dose or frequency increase of anti-TNF therapy 4 months or more after the first infusion. HCRU outcomes included CD-related surgeries, specialist visits, endoscopic or other invasive procedures, imaging tests, emergency room visits and hospitalizations. Additional outcomes included augmentation with non-biologic therapy (defined as either initiation or increase in dose of aminosalicylates or corticosteroids while on therapy with anti-TNF) and switching to another biologic therapy. Outcomes were compared between patients with and without dose escalation; statistical significance was tested using chi-square tests. Results: The study included 657 CD patients with mean (SD) age of 39.2 (13.2) years (49% male). Fifty-five percent and 45% were treated with infliximab and adalimumab, respectively. Overall, 28% (n = 183) of patients had dose escalated (incidence: 11.3 [95% CI, 9.7–13.0] per 100 patient years of anti-TNF exposure). The frequencies of HCRU outcomes among patients with and without dose escalation were as follows: surgeries (26% versus 24%, P = 0.547), specialist visits (61% versus 52%, P = 0.045), endoscopic and invasive procedures (77% versus 66%, P = 0.004), imaging tests (72% versus 64%, P = 0.082), emergency room visits (30% versus 23%, P = 0.088), and hospitalizations (39% versus 33%, P = 0.122). Both augmentation with non-biologic therapy (32% versus 19%, P = 0.001) and switching (14% versus 11%, P = 0.225) rates were higher among patients with dose escalation. Median time from dose escalation to augmentation (n = 31), switch (n = 25), and surgeries (n = 32) was 9.0, 6.0, and 9.3 months, respectively. Conclusions: This multi-country retrospective chart review study showed that over one-quarter of CD patients treated with anti-TNFs required dose escalation. HCRU was numerically higher among patients who required dose escalation during the follow-up period for all the outcomes assessed. In addition to the drug costs, future studies should take into consideration the costs of invasive procedures, imaging tests, and other measures of HCRU, including adverse events with therapies, when evaluating the cost-effectiveness of dose escalation as a strategy to recapture loss of response.